Production of hybridomas secreting monoclonal antibodies against the lympholine osteoclast activating factor. - Luben, R A (1979)
The human lympholine osteoclast activating factor (OAF) is thought to be involved in several bone-destroying diseases. The current studies were designed to produce monoclonal antibodies against OAF for use in the subsequent design of immunoassays for OAF in clinical samples. Spleen cells from mice immunized with purified human OAF were hybridized with mouse plasmacytoma cells in vitro to yield hybridomas. Several clones of these hybridomas secreted into the culture medium antibodies, which neutralized the biological activity of OAF at dilutions as high as 1:100,000 relative to the initial culture medium. These antibodies did not interfere with the activities of parathyroid hormone in the same systems. These results represent the first report of monoclonal antibodies against a human lympholine, and validate the concept that hybridoma production is a useful technique for developing antibodies against weak or scarce antigens.